2019
DOI: 10.1002/chem.201805726
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Design of Optically Active Thiophene S‐Oxides using Quantum Chemistry

Abstract: The importance of axially chiral biaryls has risen steeply in the recent decades. This structural motif proved to be successful in catalytic asymmetric synthesis and the configuration of the biaryl axis is decisive for the biological activity. A new approach for the atroposelective synthesis of biaryls would be through a cycloaddition between an enantiopure phenyl‐substituted thiophene S‐oxide and an alkyne. Importantly, the chiral center of the thiophene S‐oxide needs to be stable enough to avoid pyramidal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 84 publications
(132 reference statements)
0
7
0
Order By: Relevance
“…Dioxygenase-catalyzed oxidation of 4-methyldibenzo[b,d]thiophene 38, using wildtype Pseudomonas strains, yielded a wider range of metabolites including sulfoxide 39, benzylic alcohol 41, cis-dihydrodiol 40, sulfone 42, and aldehyde 43 (Scheme 6) [104]. A kinetic study of the racemization (130 • C) of an enantioenriched sample of sulfoxide 39 produced a higher inversion barrier (∆G = = 33.0 kcal mol −1 ) compared with benzo[b]thiophene sulfoxides 23a and 23b; it was, however, very similar to the calculated value for sulfoxide 34, ∆G = = 32.3 kcal mol −1 [64].…”
Section: Dioxygenase-catalyzed Biotransformations Of Dibenzo[bd]thiophenes 33 and 38mentioning
confidence: 62%
See 4 more Smart Citations
“…Dioxygenase-catalyzed oxidation of 4-methyldibenzo[b,d]thiophene 38, using wildtype Pseudomonas strains, yielded a wider range of metabolites including sulfoxide 39, benzylic alcohol 41, cis-dihydrodiol 40, sulfone 42, and aldehyde 43 (Scheme 6) [104]. A kinetic study of the racemization (130 • C) of an enantioenriched sample of sulfoxide 39 produced a higher inversion barrier (∆G = = 33.0 kcal mol −1 ) compared with benzo[b]thiophene sulfoxides 23a and 23b; it was, however, very similar to the calculated value for sulfoxide 34, ∆G = = 32.3 kcal mol −1 [64].…”
Section: Dioxygenase-catalyzed Biotransformations Of Dibenzo[bd]thiophenes 33 and 38mentioning
confidence: 62%
“…The preferred orientation of substrate 1g, at the TDO active site, predicted from the binding energy (−5.3 kcal mol −1 ) and the distance of the sulfur to dioxygen (2.9 Å), should yield (1S)-sulfoxide 5g. However, the low inversion barrier, predicted for sulfoxide 5g ΔG ≠ 11.2 kcal mol −1 ) [64], indicated that it would rapidly racemize, and this was confirmed by the isolation of racemic dimer 6g (Table 1). The docking of substrate 1g did not present an orientation that would lead to cis-dihydrodiol metabolite 2g, and none of the possible cis/trans-dihydrodiols 2b-g/4b-g were isolated (Table 1) [12].…”
Section: Molecular Docking Of Thiophenes 1a and 1g At The Tdo Active Sitementioning
confidence: 81%
See 3 more Smart Citations